Protein to carbohydrate (P/C) ratio changes in microbial extracellular polymeric substances induced by oil and Corexit - Shiu, Ruei-Feng; Chiu, Meng-Hsuen; Vazquez, Carlos I.; Tsai, Yi-Yen; Le, Andre; Kagiri, Agnes; Xu, Chen; Kamalanathan, Manoj; Bacosa, Hernando P.; Doyle, Shawn M.; Sylvan, Jason B.; Santschi, Peter H.; et al. (Marine chemistry, 2020)
Extracellular polymeric substances (EPS) released from marine microbial cells is a major response to stress. Most previous studies focus on the quantity of EPS released from microbes; however, the critical characteristics of EPS composition receive much less attention. Considering the complex nature and diversity of microbes in the marine system also impart distinct behaviors and reactions when exposed to stressful conditions, we cultured four phytoplankton and five bacterial species, to investigate the changes of the chemical composition of EPS under stress from a water-accommodated fraction (WAF) of oil or a chemically-enhanced WAF (CEWAF). Remaining viable cells (DNA amount) of nine marine microbes showed a higher linear negative correlation with increasing protein to carbohydrate (P/C) ratio under CEWAF than WAF treatments. The data also show that EPS with higher protein ratios was released under higher cellular stress levels induced by CEWAF, suggesting that higher protein ratio EPS, which is more hydrophobic, is secreted to physically or chemically ameliorate the hazardous agents. Our findings provide evidence that microbes can actively modify their EPS release and composition in responses to various adverse stress. Collectively, the results support the hypothesis that higher stress not only can trigger more EPS release, but also induce changes in its composition (P/C), thereby affecting environmental processes such as marine oil snow formation and the characteristic of marine organic matter. [Display omitted] •Oil and Corexit can induce the release of microbial extracellular polymeric substances (EPS).•Higher protein to carbohydrate (P/C) ratio of EPS was released at higher concentrations of oil and Corexit.•Negative correlation between microbial viability and P/C ratio was found under oil and Corexit stress.•A rapid small-volume assay protocol was established to provide assessment for P/C ratio of released EPS.